INTERNAL AND EXTERNAL FACTORS AFFECTING ISLAMIC BANKS PERFORMANCE IN NIGERIA - Aishatu Usman Muhammad (Universitas Airlangga, 2022)
The purpose of the paper is to analyze the internal and external factors affecting the performance of Islamic banking in Nigeria. The study is quantitative research that applies the generalized least square (GLS) regression to measure the effect of independent variables on the dependent variables. Data is generated from the published financial statements of the bank from the year of inception, 2012 to 2020. The dependent variables used to measure the performance are return on assets (ROA) and return on equity (ROE). The independent internal variables are measured using the financial deposit ratio (FDR) and operational efficiency ratio (OER), while the external factors are measured using gross domestic product (GDP) and inflation. The findings for the internal factors show that FDR has a positive and significant effect on performance, indicating the availability of liquidity when required by depositors. OER also showed a significant positive effect on ROA and ROE, meaning that high operational efficiency can increase efficiency and performance. Meanwhile, external factors, GDP, show a significant negative effect on performance, implying that an increase in GDP per person will increase population, decreasing real GDP. More so, inflation also showed a negative and significant effect on performance, which implies that when there is inflation, the Central Bank increases the interest rate to slow down the inflation rate. However, interest is not permissible in an Islamic bank's operation, hence not affecting its performance.